An Historical Overview of Sericulture Industry in Kashmir as an Employment and Financial Support for Economy: The Impact of Sericulture Industry on Rural Economy in Kashmir (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The silk is the final product of sericulture industry. It especially suits to rural populace working with horticulture, business visionaries and craftsmans as it requires low investment with potential for generally higher returns. It gives pay and employment to the rural poor particularly, farmers with little land-holding and minimized and more fragile areas of the general public. Kashmir is a nontraditional sericulture state delivering Mulberry and Tasar silk the bivoltine sericulture development has been one of the need divisions of Indian silk industry however its production is yet to meet the objectives. This paper for the most part centered on the performance of Sericulture in Kashmir. Sericulture industry requires low investment and it gains higher returns in short gestation period, because of this the farmers are getting pulled in to this part and it is a best instrument to improve the rural economy just as to improve their expectations for everyday comforts.